Picosecond electron beams and their features: invited paper; Proceedings of the 15th International Conference on High-Power Particle Beams, Saint-Petersburg, july 18-23, 2004 - Mesyats G. A. Gennady Andreyevich (2005, 2005)
В фонде НТБ ТПУ отсутствует